Cathode electrode, electrolytic device, and method for manufacturing a cathode electrode
Patent Information
- Application Number
- JP2022134662
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-08-26
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2042-08-26
AI Technical Summary
【0021】 本発明によれば、副生成物の生成を抑え、エチレンの選択性を高めることができる。
Smart Images

Figure 0007933362000005 
Figure 0007933362000006 
Figure 0007933362000007
Abstract
Description
[Technical Field]
[0001] This invention relates to a cathode electrode, an electrolytic device, and a method for manufacturing a cathode electrode. [Background technology]
[0002] In response to global warming, efforts are being made worldwide to reuse carbon dioxide as a new carbon source. One such effort involves electrochemically reducing carbon dioxide using electricity derived from renewable energy. For the electrochemical reduction of carbon dioxide, copper, which has a positive adsorption energy for hydrogen adsorbent species and a negative adsorption energy for carbon dioxide adsorbent species, is used as the cathode electrode. By electrochemically reducing carbon dioxide (also called electrolysis or electrolysis), it can be converted into hydrocarbons and alcohols.
[0003] Ethylene, one of the products of the electrochemical reduction of carbon dioxide, is a useful compound used as a precursor in various chemical products such as resins. While ethylene is separated from naphtha, a petroleum product, producing chemical products from non-fossil fuels is necessary to realize a fossil-free society. Therefore, obtaining ethylene from carbon dioxide is extremely important.
[0004] Various studies have been conducted to improve ethylene selectivity, including controlling the structure of catalysts, adding dopants, and optimizing electrolytic cells. For example, Patent Document 1 describes the use of crystalline copper phthalocyanine as the cathode electrode. Non-Patent Document 1 reports that modifying the copper surface with a hydrophobic polymer improved ethylene selectivity. Furthermore, Non-Patent Document 2 reports that treating the copper surface with 1-octadecanethiol to impart superhydrophobicity improved ethylene selectivity. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Japanese Patent Publication No. 2018-141227 [Non-patent literature]
[0006] [Non-Patent Document 1] Jianchun Wang and 8 others, “Selective CO2 Electrochemical Reduction Enabled by a Tricomponent Copolymer Modifier on a Copper Surface”, J. Am. Chem. Soc., 143, 7, 2857-2865, 2021. [Non-Patent Document 2] David Wakerley and 7 others, “Bio-inspired hydrophobicity promotes CO2 reduction on a Cu surface”, Nature Materials, 18, 1222-1227, 2019 [Overview of the Initiative] [Problems that the invention aims to solve]
[0007] Although ethylene selectivity has improved through the aforementioned studies, existing copper catalysts produce many by-products, and there is still room for improvement in ethylene selectivity.
[0008] The present invention has been made in view of the above circumstances, and aims to provide a cathode electrode, an electrolytic apparatus, and a method for manufacturing a cathode electrode that can suppress the generation of by-products and improve the selectivity of ethylene. [Means for solving the problem]
[0009] A cathode electrode according to a first aspect of the present invention is A polymer layer containing an anion-conducting polymer, The polymer layer coated First Copper and to have death, The anion-conducting polymer has the structure shown in formula (I). do. [ka]
[0011] The cathode electrode according to the first aspect of the present invention described above is Second It further comprises a porous carbon material that supports copper, It would be acceptable to do so.
[0012] The aforementioned Second Copper is, Supported on the surface of the carbon material, It would be acceptable to do so.
[0014] An electrolytic apparatus according to a second aspect of the present invention is The present invention is provided with a cathode electrode according to the first aspect of the present invention described above.
[0015] The electrolytic apparatus according to the second aspect of the present invention described above is: Electrolyzing carbon dioxide, It would be acceptable to do so.
[0016] A method for manufacturing a cathode electrode according to a third aspect of the present invention is: The process includes a coating step of coating the surface of copper with a polymer layer containing an anion-conducting polymer. fruit, The anion-conducting polymer has the structure shown in formula (I). . [ka]
[0017] The method for manufacturing a cathode electrode according to the third aspect of the present invention described above is: The method further includes an exchange step of exchanging anions contained in the polymer layer coating the copper for hydroxide ions. It would be acceptable to do so.
[0020] The method for manufacturing a cathode electrode according to the third aspect of the present invention described above is: The process further includes a potential scanning step of applying a potential to the copper in a range in which oxidation and reduction are repeated in the presence of halogen ions. It would be acceptable to do so. A method for manufacturing a cathode electrode according to a fourth aspect of the present invention is: A coating step in which the surface of copper is covered with a polymer layer containing an anion-conducting polymer, An exchange step of replacing the anions contained in the polymer layer coating the copper with hydroxide ions, Includes. A method for manufacturing a cathode electrode according to a fifth aspect of the present invention is: A coating step in which the surface of copper is covered with a polymer layer containing an anion-conducting polymer, A potential scanning step in which oxidation and reduction are repeatedly performed on the copper in the presence of halogen ions, Includes. [Effects of the Invention]
[0021] According to the present invention, the generation of by-products can be suppressed and the selectivity of ethylene can be improved. [Brief explanation of the drawing]
[0022] [Figure 1] This figure shows the configuration of an electrolytic device according to an embodiment of the present invention. [Figure 2] This figure shows the nuclear magnetic resonance (NMR) spectrum of the anion-conducting polymer according to Example 1. [Figure 3] This figure shows the Faraday efficiency (FE) of each product according to Example 1. [Figure 4] This figure shows scanning electron microscope (SEM) images of electrodes according to Example 2. (A) shows an SEM image of carbon paper (CP). (B) shows an SEM image and conceptual diagram of Cu / CPs, in which copper is supported on the surface of CP. (C) shows an SEM image and conceptual diagram of Cu / CPf, in which copper is supported on the surface of CP and inside the porous structure. [Figure 5] This figure shows the FE of each product according to Example 2. [Figure 6] This figure shows SEM images of electrodes according to Example 3. (A) shows an SEM image of CuCube / CPs in which cubic copper nanoparticles are supported on the surface of CP. (B) shows SEM images of CuCube / CPs prepared at different potential scanning speeds. [Figure 7] This figure shows the ratio of ethylene FE to methane FE in CuCube / CPs. [Figure 8] This figure shows SEM images of the electrodes according to Example 3. (A) and (B) show SEM images of CuNPs / CPs and CuNPsno KCl / CPs, respectively, in which copper nanoparticles are supported on the surface of CP. [Figure 9] This figure shows the X-ray diffraction (XRD) pattern of the electrode according to Example 3. [Figure 10] This figure shows the surface roughness factor of the electrode according to Example 3. [Figure 11] This figure shows the ratio of ethylene FE to methane FE for CuCube / CPs, CuNPs / CPs, and CuNPsno KCl / CPs. [Modes for carrying out the invention]
[0023] Embodiments of the present invention will be described with reference to the drawings. However, the present invention is not limited to the embodiments and drawings described below. In the embodiments described below, expressions such as “having,” “including,” or “containing” also include the meaning of “consisting of” or “composed of.”
[0024] As shown in Figure 1, the electrolytic apparatus 10 according to this embodiment comprises an electrolytic cell 1, an electrolyte membrane 2, a cathode cell 3, an anode cell 4, a cathode electrode 5, an anode electrode 6, and an application unit 7. The electrolyte membrane 2 is an anion exchange membrane, and OH - This is a membrane through which anions such as can pass. The electrolytic cell 1 is divided into a cathode tank 3 and an anode tank 4 by an electrolyte membrane 2. The cathode tank 3 and anode tank 4 are filled with electrolyte solution 8. Preferably, the electrolytic device 10 is used for the electrolysis of carbon dioxide. In the case of carbon dioxide electrolysis, potassium bicarbonate is used as the electrolyte solution 8.
[0025] The cathode electrode 5 is held inside the cathode tank 3, and when electrolyte 8 is added to the cathode tank 3, the cathode electrode 5 is exposed to the electrolyte 8. The anode electrode 6 is held inside the anode tank 4, and when electrolyte 8 is added to the anode tank 4, the anode electrode 6 is exposed to the electrolyte 8. The application unit 7 connects the cathode electrode 5 and the anode electrode 6 via a circuit. The application unit 7 applies a potential between the cathode electrode 5 and the anode electrode 6.
[0026] When carbon dioxide (CO2) is circulated through the cathode tank 3 and the application unit 7 applies a potential between the cathode electrode 5 and the anode electrode 6, hydroxide ions (OH) are generated in the anode tank 4. - ) is oxidized to oxygen (O2) and electrons (e - ) is produced. Electrons move through the circuit to the cathode electrode 5, and the catalytic action on the surface of the cathode electrode 5 reduces carbon dioxide, producing various compounds such as ethylene (C2H4) and methane (CH4). In parallel with the reduction of carbon dioxide, the hydrogen evolution reaction also occurs simultaneously.
[0027] In the electrolysis of carbon dioxide, the anode electrode 6 can be made of, for example, iridium oxide, nickel, or platinum. On the other hand, the cathode electrode 5 contains a polymer layer containing an anion-conducting polymer and copper (Cu) coated with the polymer layer. The anion-conducting polymer is not particularly limited as long as it is a polymer that has the property of conducting anions. The anion-conducting polymer is, for example, a polymer having an imidazolium group, a pyridinium group, a phosphonium group, or a quaternary ammonium group. Preferably, the anion-conducting polymer has a quaternary ammonium group. As an anion-conducting polymer, the chlorine derived from VBC in a polymer copolymerized with styrene and 4-vinylbenzyl chloride (VBC) is quaternized and treated with KOH to remove Cl - OH - An example of a polymer that has undergone ion exchange is given.
[0028] The cathode electrode 5 may further comprise a porous carbon material supporting copper. Examples of porous carbon materials include CP. The copper may be supported on the surface of the carbon material, or it may be supported on the surface of the carbon material as well as further within the porous structure of the carbon material.
[0029] Herein, a method for manufacturing the cathode electrode 5 according to this embodiment will be described. The manufacturing method includes a coating step of coating the surface of copper with a polymer layer containing an anion-conducting polymer. The shape of the copper is not particularly limited, and can be, for example, a flat plate or a thin piece. The surface of the copper may be polished before coating it with the polymer layer. Known methods can be used to coat the surface of the copper with the polymer layer, for example, the spin coating method.
[0030] In the spin coating method, a polymer solution is dropped onto a rotating copper plate. The thickness of the polymer layer can be controlled by controlling the rotation speed of the copper plate. Specifically, a faster rotation speed allows for the formation of a thinner polymer layer, while a slower rotation speed allows for the formation of a thicker polymer layer. The rotation speed of the copper plate in the spin coating method is, for example, 500-5000 rpm, 1000-4500 rpm, 2000-4000 rpm, or 2500-3500 rpm. Preferably, the rotation speed of the copper plate in the spin coating method is 3000 rpm. In the coating step, the solvent contained in the polymer solution may be removed by heat treatment.
[0031] The manufacturing method may further include an exchange step of exchanging anions contained in the polymer layer coating the copper for hydroxide ions. The above-mentioned KOH treatment is preferred for the exchange step. In the KOH treatment, the copper coated with the polymer layer is immersed in a KOH solution.
[0032] When the cathode electrode 5 comprises a porous carbon material, one method for supporting copper on the carbon material is electrodeposition. In electrodeposition, the electrode containing the carbon material and a platinum electrode as a counter electrode are held in an electrolyte 8 containing copper in an electrolytic cell, and copper can be deposited on the carbon material by applying a potential between the electrodes. The electrolyte 8 contains, for example, CuSO4 and H2SO4. The electrodeposition conditions are set as appropriate.
[0033] To support copper within the porous structure of a carbon material, Cu must be deposited into the hydrophobic porous structure. In this case, before electrodeposition, the carbon material can be immersed in an organic solvent miscible with water, and air bubbles inside the porous structure can be removed using ultrasound or other methods. The organic solvent that has penetrated into the porous structure in this way can be replaced with water by immersing the carbon material in water. After replacement with water, copper can be supported within the porous structure of the carbon material by electrodeposition as described above.
[0034] Potential cycling may be performed on the copper to control the nanostructure of the copper surface before or after coating with a polymer layer. Potential cycling can cause nanoparticles to form on the copper surface. That is, the manufacturing method may further include a potential scanning step of applying a potential to the copper in a range in which oxidation and reduction are repeated in the presence of halogen ions.
[0035] In the potential scanning step, an electrode containing copper and a platinum electrode as a counter electrode are held in the electrolyte 8 in the electrolytic cell, and a potential is applied between the electrodes. Examples of halogen ions include fluoride ions, chloride ions, and bromide ions. When chloride ions are used as halogen ions, the electrolyte 8 contains, for example, KCl and KHCO3. The potential scanning range is -0.7 to 0.9 V relative to the reversible hydrogen electrode (RHE).
[0036] In the reduction reaction of carbon dioxide, it has been shown that methane production depends on the pH of the reaction field, with selectivity improving at low pH, while ethylene production is pH independent. As shown in the equation below, in the reduction reaction of carbon dioxide, many hydroxide ions are generated during reduction, and the pH near the catalyst surface increases. 2CO2 + 8H2O + 12e - →C2H4+12OH -
[0037] By controlling the mass transfer characteristics of hydroxide ions generated by the reaction and increasing the pH of the reaction field, methane production can be suppressed and relative ethylene selectivity can be improved. A higher pH also leads to a lower proton concentration, which can suppress the competitive hydrogen production reaction. According to the electrolytic apparatus 10 of this embodiment, hydroxide ions are conducted by the polymer layer containing an anion-conducting polymer in the cathode electrode 5, allowing the pH of the reaction field to be controlled to an optimal pH for ethylene production. Therefore, the generation of by-products such as hydrogen can be suppressed, and the selectivity of ethylene can be enhanced.
[0038] In the reduction reaction of carbon dioxide, differences in mass transfer and pH gradient due to the microstructure of the electrode significantly affect the distribution of the product. The electrolytic apparatus 10 according to this embodiment may further include a porous carbon material supporting copper. This allows control over the manner in which copper is supported in the porous structure, thereby controlling the microstructure of the surface of the cathode electrode 5 and improving the selectivity of ethylene.
[0039] In this embodiment of the electrolytic device 10, the cathode electrode 5 is exposed to carbon dioxide dissolved in the electrolyte 8. However, gaseous carbon dioxide may be supplied to the cathode tank 3, exposing the cathode electrode 5 to gaseous carbon dioxide. An example of such an embodiment is a solid cell. In a solid cell, a membrane electrode assembly is used in which the cathode electrode 5 and the anode electrode 6 are joined to an electrolyte membrane 2. Water vapor, water, or the electrolyte 8 is supplied to the anode electrode 6, and carbon dioxide gas is supplied to the cathode electrode 5. When carbon dioxide gas is supplied to the cathode electrode 5, the cathode electrode 5 may be humidified with water vapor.
[0040] The present invention will be described in more detail by the following examples, but the present invention is not limited to these examples. [Examples]
[0041] Example 1: Investigation of anion-conducting polymer-coated Cu electrodes (Synthesis of anionic conductive polymers) Poly(VBC-co-St), a precursor to the final product, was synthesized by copolymerizing styrene with 4-vinylbenzyl chloride (VBC). This reaction is a radical-free reaction initiated by azobisisobutyronitrile (AIBN). Toluene was used as the solvent.
[0042] 5.05 mL of styrene, 0.83 mL of VBC, 0.023 g of AIBN, and 10 mL of toluene were weighed out and reacted at 70°C for 24 hours. The reaction mixture was concentrated in an evaporator, reprecipitated with ethanol for 1 hour, and vacuum dried for 3 hours. The product was recovered, and the synthesis of poly(VBC-co-St) was confirmed by NMR, and the average molecular weight Mn was measured by gel permeation chromatography (GPC).
[0043] To quaternize the chlorine derived from VBC, 10 mL of trimethylamine (TMA) was added to 1 g of poly(VBC-co-St) and reacted at 60°C for 24 hours. After removing some of the TMA in an oil bath, pure water was added and the mixture was washed for 18 hours to remove any remaining TMA. The mixture was concentrated in an evaporator, vacuum dried for 3 hours, and then subjected to NMR measurement.
[0044] (Polymer coating by spin coating method) The surface of a copper flake was electropolished in a phosphoric acid solution (2.0 V, 10 minutes). A 10 wt% methanol solution of the synthesized polymer (VBTAC) was dropped onto the polished copper surface, and the copper surface was coated with VBTAC by spin coating (3000 rpm). The temperature was raised to 130°C for 2 minutes, then raised to 50°C for 30 minutes to remove the solvent. The resulting copper flake was immersed in a 1 M KOH solution for 1 hour to perform ion exchange of VBTAC.
[0045] (Carbon dioxide electrolysis test) A carbon dioxide electrolysis test was conducted using a sandwich-type flow cell. The sandwich-type flow cell consists of an ion exchange membrane sandwiched between a cathode tank containing a VBTAC-coated copper flake (the cathode electrode) and an anode tank containing a platinum flake (the anode electrode). The surface area of both the copper and platinum flakes is 1 cm². 2 The cathode and anode tanks each held 1.5 mL of potassium bicarbonate solution as the electrolyte. Sustainion™ X37-50 Grade-RT was used as the ion exchange membrane. The ion exchange membrane was pre-treated by immersing it in 1 M KOH for two days. In the electrolysis test, -1.1 to -1.3 V (vs. RHE) was applied for 30 minutes each. For comparison, carbon dioxide electrolysis tests were also performed on copper flakes not coated with VBTAC and on copper flakes not coated with VBTAC that had been immersed in 1 M KOH solution for one hour.
[0046] The product in the cathode tank was quantified using gas chromatography (GC) based on a pre-prepared calibration curve. A GC2030 gas chromatograph (Shimadzu Corporation) was used, and the flow rate was measured with a precision membrane flow meter (Horiba, Ltd.). The GC analysis conditions were as follows:
[0047] Column: micropacked ST (manufactured by Shinwa Chemical Co., Ltd.) Detector: Barrier discharge ionization detector BID-2030 Control pressure: 200.0 kPa Purge flow rate: 3.0 mL / min Sample injection volume: 1 mL Sample introduction method: Split injection with a split ratio of 10. Column heating program: After sample injection, maintain a constant temperature of 35°C for 2 minutes → increase temperature at 25°C / min → maintain a constant temperature of 220°C.
[0048] Given the molar concentration φ (mol / mL), flow rate V (mL / s), number of electrons in the reaction n, Faraday constant F (C / mol), and electron flow I (C / s), FE was calculated for each product using the following formula. FE(%) = φ·V·n·F·100 / I
[0049] (Results) Figure 2 shows the NMR spectrum of VBTAC. The copolymerization ratio of VBTAC was calculated from the NMR spectrum, and the ion exchange capacity (IEC) was calculated. As a result, the copolymerization ratio was 92:8 (styrene:VBTAC), and the IEC was 0.73 meq.
[0050] Figure 3 shows the FE at each cathode electrode. The ethylene production ratio in the carbon dioxide reduction product (gas) was 56% with KOH treatment, whereas it was 66% with the VBTAC-coated copper plate.
[0051] Example 2: Control of Microstructure of Cu Electrode (Cu / CP s Preparation) Copper was electrodeposited on CP (manufactured by Toray Industries, Inc., TGPH-060). The electrode exposed portion to the electrolytic solution was a 13 mm square (geometric surface area: 169 mm 2 ). A single-chamber cell was used as the electrolytic cell. Using 70 mL of an electrolytic solution containing 0.01 M CuSO4 (manufactured by Wako Pure Chemical Industries, Ltd.) and 1 M H2SO4 (manufactured by Wako Pure Chemical Industries, Ltd.), the electrodeposition conditions were 2 mA (1.18 mA / cm 2 ) for 20 minutes. The counter electrode was a platinum foil, and the reference electrode was Ag / AgCl / saturated KClaq. The stirring speed was 200 rpm.
[0052] (Cu / CP f Preparation) To produce an electrode in which Cu is deposited to the inside of CP, which is a hydrophobic porous electrode, an isopropanol (IPA) permeation treatment was performed before electrodeposition. First, CP cut into 13 mm × 30 mm was placed in a vial, filled with IPA (manufactured by Wako Pure Chemical Industries, Ltd.), and subjected to ultrasonic waves for 10 minutes. This allowed IPA to permeate into the CP pores to remove air bubbles. Next, the CP was taken out and submerged in a petri dish filled with RO water, the IPA filling the inside of the pores was replaced with water, so that both sides of the CP were exposed in a 13 mm square shape. The concentration of CuSO4 in the electrolytic solution, the electrodeposition conditions, and the stirring speed were 0.1 M, 100 mA (59.2 mA / cm 2), and instead of 400rpm, Cu / CP f Electrodeposition was performed in the same manner as before. After electrodeposition, only one side of the electrode, measuring 13 mm x 13 mm, was exposed.
[0053] (Preparation of copper thin sections) Measurements using commercially available copper thin sheets (0.1 mm thick, manufactured by Alfa Aesar) with only one side (13 mm x 13 mm) exposed were performed using fresh copper thin sheets every time to eliminate the effects of surface oxidation.
[0054] (Carbon dioxide electrolysis test) The obtained Cu / CP s and Cu / CP f Alternatively, a carbon dioxide electrolysis test was performed using an H-type electrolytic cell with a copper flake as the cathode electrode. The electrode and Sustainion™ X37-50 Grade-RT anion exchange membrane were fixed to the H-type electrolytic cell, and 30 mL of electrolyte (0.1 M KHCO3) was placed in both the anode and cathode chambers. A platinum mesh was used for the anode electrode. The reference electrode was set to Ag / AgCl / saturated KCl, and the carbon dioxide flow rate was set to 20 sccm. The stirring speed of the cathode chamber was set to 500 rpm.
[0055] Carbon dioxide was bubbled into both the anode and cathode tanks for approximately 30 minutes. The pH of the electrolyte was measured to confirm saturation with carbon dioxide (pH 6.8). The gas outlet of the cathode tank was connected to the MGS of the GC, and the outlet of the MGS was connected to a membrane flow meter. A potentiostat HZ-5000 (manufactured by Hokuto Denko Co., Ltd.) was connected to the electrode, and chronoamperometry (potential-constant electrolysis) was started at the measured potential. After 30 minutes, 1 mL of the gas from the cathode tank flowing through the MGS was introduced into the GC column, and the gas products were analyzed. The peak areas of each product (H2, CO, CH4, and C2H4) were read and recorded from the gas chromatogram.
[0056] Using a scanning electron microscope (SEM, S-4800 (Hitachi, Ltd.)), CP and Cu / CP s and Cu / CP fThe following was observed. Fiji ImageJ 2.1.0 / 1.53c was used for analysis. Cu thin section, Cu / CP s and Cu / CP f For each case, FE was calculated similarly using the formula described in Example 1 above.
[0057] (Calculation of electric potential) Measured Ag / AgCl reference potential E Ag / AgCl The standard electrode potential E of the Ag / AgCl electrode 0 Ag / AgCl The potential E relative to the reversible hydrogen electrode is calculated using (=0.197) and the pH of the electrolyte (=6.8). RHE It was converted to [this]. E RHE =E Ag / AgCl +0.197 + 0.059 × 6.8 Furthermore, the measured solution resistance R s The potential E is calculated by subtracting the solution resistance using [Ω]. RHE(iR free) The result was calculated. E RHE(iR free) =E Ag / AgCl -i×R s +0.197 + 0.059 × 6.8
[0058] (result) Figures 4(A), (B), and (C) show CP and Cu / CP, respectively. s and Cu / CP f The SEM image of Cu / CP is shown. s In contrast, Cu was precipitated on the surface exposed to the outside. f Therefore, in addition to the surface exposed on the outside, Cu was also precipitated inside the CP.
[0059] Figure 5 shows a Cu thin section and Cu / CP. s and Cu / CP f This shows the FE of Cu / CP s FE was the highest.
[0060] Example 3: Control of the nanostructure of Cu electrodes (CuCube / CP s (Production of) Cu / CP sThe redox potential cycle was swept to form cubic nanoparticles. Similar to Example 2, Cu / CP s The following was performed: The sample was fabricated, and the subsequent potential cycle was carried out under the following conditions.
[0061] Potential cycling conditions Electrolyte: 4mM KCl+0.1M KHCO3 (CO2 distribution) Opposite pole: Platinum flakes Reference electrode: Ag / AgCl / saturated KCl Stirring speed: 200 rpm Potential scanning speed: 1, 5, or 25 mV / s Potential scanning range: -0.7V~0.9V vs.RHE Number of potential scans: CV is performed from the open-circuit potential (OCP) in the order of positive → negative, stopping during the negative sweep on the 5th cycle.
[0062] The resulting CuCube / CP s We observed CuCube / CP using SEM. s A carbon dioxide electrolysis test similar to that in Example 2 was performed using the same method, and the FE was evaluated.
[0063] (result) Figure 6(A) shows CuCube / CP s The SEM image is shown. As shown in Figure 6(B), CuCube / CP s On the surface, cubic nanoparticles of varying sizes were formed depending on the potential scanning speed. The average particle sizes were 126.0 nm, 66.4 nm, and 31.6 nm at potential scanning speeds of 1 mV / s, 5 mV / s, and 25 mV / s, respectively.
[0064] CuCube / CP s Figure 7 shows the ratio of FE of ethylene to FE of methane. The larger the particle size, the greater the FE of ethylene compared to the FE of methane. This suggests that the number of sites favorable for ethylene formation increased with increasing particle size.
[0065] (CuNPs / CP s (Production of) CuCube / CP s In the fabrication conditions, the potential scanning range of the potential cycle is changed from 0.4V to 0.9V to 0.4V to 0.9V to ensure oxidation only. s We fabricated it. In addition, by using an electrolyte that does not contain KCl in the potential cycle, CuNPs no KCl / CP s I made it.
[0066] Obtained CuNPs / CP s and CuNPs no KCl / CP s We observed it with an SEM. Cu / CP s CuCube / CP s CuNPs / CP s and CuNPs no KCl / CP s The surface was analyzed using XRD.
[0067] Cu / CP s CuCube / CP s and CuNPs no KCl / CP s The electrochemical surface area (ECSA) was evaluated. With capacitance C, the relationship Q = CV holds between charge Q and voltage V. From this relationship, the sweep rate v [V / s] when the potential is swept across the electrode at a constant sweep rate and the current density i due to charging of the electric double layer were determined. DLC The relationship between these two is derived. v=dV / dt=dQ / C DLC dt=i DLC / C DLC
[0068] From this formula, the capacitance of the electric double layer in the electrode (electric double layer capacitance) C is obtained. DLC [μF / cm 2 The following is required. In this embodiment, a cyclic voltammogram (CV) was performed by changing the sweep rate v in the potential region of a non-Faraday current due to electric double-layer capacitance charging, and the electric double-layer capacitance (CDLC) was determined. If the electrode material is the same, the capacitance is proportional to the electrochemical surface area of the electrode. Assuming that the surface of all electrodes used in this embodiment is Cu, the electrode roughness was determined from the ratio of the electric double-layer capacitances of each electrode, and the ECSA was compared.
[0069] The requirements for CV are as follows: Electrolyte: 0.1M HClO470mL Opposite pole: Platinum flakes Reference electrode: Ag / AgCl / saturated KClaq Potential scanning speed: 50, 100, 150, 200, 250 mV / s
[0070] First, electrolyte was placed in a single-chamber cell and the electrodes were fixed, and it was bubbled with N2 for 30 minutes. CV was performed by varying the potential scanning speed within a potential range of 50 mV where no Faraday current flowed. From the difference in currents i1 and i2 at two points at the center potential of the measured potential range, the current density due to charging of the electric double layer i was calculated using the following formula. DLC [mA / cm 2 ] was sought. i DLC =|i1-i2| / 2 With the potential scanning speed v [V / s] on the horizontal axis, i DLC The slope of the plotted graph shows the electrical double layer capacitance C. DLC [μF / cm 2 The electrical double layer capacitance C of the Cu thin film was calculated. REF The roughness factor (RF) was determined from the ratio. RF=C DLC / C REF
[0071] Furthermore, the obtained CuNPs / CP s and CuNPs no KCl / CP s A carbon dioxide electrolysis test similar to that in Example 2 was performed using the same method, and the FE was evaluated.
[0072] (result) CuNPs / CP s and CuNPs no KCl / CP s The SEM images of CuNPs / CP are shown in Figure 8(A) and Figure 8(B), respectively. s and CuNPs no KCl / CP s It was found that disordered nanoparticles were formed on the surface.
[0073] The XRD pattern is shown in Figure 9. CuCube / CP s and CuNPs / CP s exhibited detected diffraction lines of Cu2O. The surface roughness factor RF is shown in Figure 10. CuCube / CP s had a lower degree of roughness than CuNPs no KCl / CP s .
[0074] Figure 11 shows the ratio of ethylene FE to methane FE for CuCube / CP s , CuNPs / CP s and CuNPs no KCl / CP s . The ethylene / methane ratio of CuCube / CP s was the highest. From the above, it was suggested that the abundance of the Cu(100) plane and Cu2O contributes to high ethylene selectivity.
[0075] The above-described embodiments are for illustrating the present invention, and do not limit the scope of the present invention. That is, the scope of the present invention is indicated by the claims rather than the embodiments. Various modifications made within the scope of the claims and within the meaning equivalent to the invention are considered to fall within the scope of the present invention.
Industrial Applicability
[0076] The present invention is useful for the production of ethylene.
Description of Symbols
[0077] 1 Electrolytic cell, 2 Electrolyte membrane, 3 Cathode chamber, 4 Anode chamber, 5 Cathode electrode, 6 Anode electrode, 7 Application unit, 8 Electrolyte solution, 10 Electrolysis device
Claims
1. A polymer layer containing an anion-conducting polymer, The first copper coated with the polymer layer, It has, The anion-conducting polymer has the structure shown in formula (I), 【Chemistry 1】 Cathode electrode.
2. Further comprising a porous carbon material supporting a second copper, The cathode electrode according to claim 1.
3. The second copper is, Supported on the surface of the carbon material, The cathode electrode according to claim 2.
4. A cathode electrode comprising the one described in any one of claims 1 to 3, Electrolyzer.
5. Electrolyzing carbon dioxide, The electrolytic apparatus according to claim 4.
6. The process includes a coating step of coating the surface of copper with a polymer layer containing an anion-conducting polymer, The anion-conducting polymer has the structure shown in formula (I), 【Chemistry 2】 A method for manufacturing a cathode electrode.
7. The method further includes an exchange step of exchanging anions contained in the polymer layer coating the copper for hydroxide ions. The method for manufacturing a cathode electrode according to claim 6.
8. The process further includes a potential scanning step of applying a potential to the copper in a range in which oxidation and reduction are repeated in the presence of halogen ions. A method for manufacturing a cathode electrode according to claim 6 or 7.
9. A coating step of coating the surface of copper with a polymer layer containing an anion-conducting polymer, An exchange step of replacing the anions contained in the polymer layer coating the copper with hydroxide ions, A method for manufacturing a cathode electrode, including [the specified part of the invention].
10. A coating step of coating the surface of copper with a polymer layer containing an anion-conducting polymer, A potential scanning step in which oxidation and reduction are repeatedly performed on the copper in the presence of halogen ions, A method for manufacturing a cathode electrode, including [the specified part of the invention].
Citation Information
Patent Citations
Method for manufacturing ethylene selectively from carbon dioxide
JP2004176129A
Method for producing ethylene in larger amount by electrochemically reducing carbon dioxide, electrolytic apparatus, carbon dioxide reduction electrode and carbon dioxide reduction catalyst
JP2018141227A
Electrode material, method of producing electrode material, and reduction reaction device
JP2019085608A
Electrode catalyst layer for carbon dioxide electrolysis cell, and electrolysis cell and electrolysis device having same
JP2020132965A
Electrode catalyst layer for carbon dioxide electrolysis cell, as well as electrolysis cell and electrolytic device for carbon dioxide electrolysis equipped with the same
JP2021147677A